2011
DOI: 10.1080/00224540903366453
|View full text |Cite
|
Sign up to set email alerts
|

Coping Resources, Perceived Stress and Adjustment to Divorce Among Israeli Women: Assessing Effects

Abstract: The aim of this study was to examine how socioeconomic resources (level of education and evaluation of economic situation), cognitive resources (sense of coherence), emotional resources (the quality of relationship with the ex-spouse and the existence of a new romantic relationship), and perceived stress contribute to explaining the adjustment of Israeli women to divorce. Adjustment to divorce was examined along four dimensions: self-acceptance of divorce, disentanglement of the love relationship, symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
1
23
0
1
Order By: Relevance
“…Previous research showed that adults who experienced divorce reported psychological growth when measured by the PTGI (Krumrei, Mahoney, & Pargament, 2009). More specifically, divorced adults exhibited an increased sense of autonomy and competence, more developed coping skills, more life reflection skills, more self-confidence, a sense of coherence and optimism, and new life perspectives in consequence of marital dissolution (King & Raspin, 2004;Kulik & Heine-Cohen, 2011;Sakraida, 2005;Thomas & Ryan, 2008).…”
Section: The Present Studymentioning
confidence: 99%
“…Previous research showed that adults who experienced divorce reported psychological growth when measured by the PTGI (Krumrei, Mahoney, & Pargament, 2009). More specifically, divorced adults exhibited an increased sense of autonomy and competence, more developed coping skills, more life reflection skills, more self-confidence, a sense of coherence and optimism, and new life perspectives in consequence of marital dissolution (King & Raspin, 2004;Kulik & Heine-Cohen, 2011;Sakraida, 2005;Thomas & Ryan, 2008).…”
Section: The Present Studymentioning
confidence: 99%
“…Perceived stress has also been found to relate to an assortment of psychosocial and physiological constructs, such as personality (Besser & Shackelford, 2007;Burgess, Irvine, & Wallymahmed, 2010;Candrian et al, 2008;Ebstrup, Eplov, Pisinger, & Jørgensen, 2011), affect (Besser & Shackelford, 2007;Cohen et al, 1993;Davidsdottir, 2007), self-efficacy (Ebstrup et al, 2011;Moeini et al, 2008;Trouillet, Gana, Lourel, & Fort, 2009), attachment (Cordon, Brown, & Gibson, 2009;Koopman et al, 2000;McCarthy, Moller, & Fouladi, 2001;Reiner, Anderson, Hall, & Hall, 2010), adjustment (Baker, 2004;Curtis, Groarke, Coughlan, & Gsel, 2004;Extremera, Durán, & Rey, 2007;Kulik & Heine-Cohen, 2011), depression (Candrian et al, 2008;Ghorbani, Krauss, Watson, & LeBreton, 2008;Holt-Lunstad, Birmingham, & Light, 2011), happiness (Brief, Burke, George, Robinson, & Webster, 1988;Chatters, 1988;Feist, Bodner, Jacobs, Miles, & Tan, 1995;Schiffrin & Nelson, 2010), health related behavior (Naquin & Gilbert, 1996;Rod, Grønbaek, Schnohr, Prescott, & Kristensen, 2009;Wichianson, Bughi, Unger, Spruijt-Metz, & Nguyen-Rodriguez, 2009), and health problems (Cohen et al, 1993;Lovell, Moss, Wetherell, 2011;Nielsen et al, 2008).…”
Section: Correlates Of Perceived Stressmentioning
confidence: 99%
“…Many authors have also used instruments they have developed specifically for the particular setting of their study (e.g. Beatty et al, 2009;Besser & Shackelford, 2007;Kulik & Heine-Cohen, 2011). With objective conceptualizations of stress providing an incomplete picture (Cohen et al, 1983), and with moderating and mediating variables between stressors and coping mechanisms (e.g.…”
Section: Measures Of Perceived Stressmentioning
confidence: 99%
“…Additionally, the very low correlation between the Coparenting Conflict subscale with the Lonely-Negativity subscale (r = .14, p \ .01) and the non-significant correlation between the Coparenting Conflict subscale with the Former Partner Attachment subscale (r = .05, ns) found in that study may also suggest that coparenting conflict may be not a nuclear dimension of the PAD latent construct. Therefore, considering past research on the dimensions of PAD (e.g., Kramrei et al 2007;Kulik and Heine-Cohen 2011), as well as the recent theoretical contributions that outlined coparenting as a universal family process (Feinberg 2003;Lamela et al 2010a, b), in the current study, we assumed that lonely-negativity and former partner attachment would be the only two components that reflect PAD.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Past studies have demonstrated that divorced adults with higher scores in the indicators of PAD proposed by Sweeper and Halford (2006) reported a greater subjective well-being and fewer psychopathology symptoms as well. Subjective well-being is moderately associated with a higher forsaken of the life goals previous to divorce (King and Raspin 2004), a weaker emotional attachment to the ex-spouse (Kulik and Heine-Cohen 2011), an increase of social relationships (Kramrei et al 2007), a new satisfactory intimate relationship (Kulik and Heine-Cohen 2011), and a cooperative coparenting relationship (Yárnoz-Yaben and González 2010).…”
Section: Psychological Adjustment To Divorce (Pad)mentioning
confidence: 99%